Generación de fractales a partir del método de Newton - Marín, María José; Giménez, Fernando; Monsoriu, Juan A. (Modelling in science education and learning, 2013)
A large number of fractals known, as Julia fractals and Mandelbrot, can be generated from an iterative method. In this paper we present a virtual laboratory developed as a Graphical User Interface (GUI) of Matlab that allows us to study and visualize in real time the relationship between Newton iterative methods of two variables and the generation of fractals. The main objective is to allow Technical School students in Numerical Computation subjects to acquire the skills to generate fractals and interpret their plots in terms of the convergence or divergence speed of the sequence of iterated.